2021
DOI: 10.3390/ijerph18020585
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on the Relationship between Body Dissatisfaction and Morbid Exercise Behaviour

Abstract: Background: The present study aimed to quantify the relationship between body dissatisfaction and morbid exercise behaviour (MEB). Methods: The electronic databases MEDLINE, PsycINFO, Web of Science, SciELO, and Dissertations & Theses Global were searched from inception to September 2020. Pooled effect sizes corrected for sampling errors (r+) were computed using a bare-bones meta-analysis. The robustness of the results was examined by influence analyses. The presence of moderators was examined by inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Body dissatisfaction may be defined as a state of displeasure concerning the overall shape and size of one’s own body in general, as well as of those regions that are of greatest concern to those with eating disorders (e.g., buttocks, stomach, thighs, hips) [ 26 , 27 ]. These aspects may favour morbid exercise modalities through both negative reinforcement (e.g., to avoid the guilt of not having done enough to compensate for the caloric intake), and positive reinforcement (e.g., to obtain a more toned or thin body) [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body dissatisfaction may be defined as a state of displeasure concerning the overall shape and size of one’s own body in general, as well as of those regions that are of greatest concern to those with eating disorders (e.g., buttocks, stomach, thighs, hips) [ 26 , 27 ]. These aspects may favour morbid exercise modalities through both negative reinforcement (e.g., to avoid the guilt of not having done enough to compensate for the caloric intake), and positive reinforcement (e.g., to obtain a more toned or thin body) [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review also did not include studies focused on body image, which is distinct from yet related to weight stigma and its internalization (77) and has been examined more extensively in relation to PA (78). Prior findings pertaining to PA, body dissatisfaction, and other factors related to eating disorders (including compulsive exercise) may inform the understanding of the relationship between weight stigma and PA (79). More stringent inclusion criteria in relation to study quality (e.g., sample size) were not imposed because of prior knowledge of the limited number of studies on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The review collated data from studies employing the most widely used self-report instruments for the assessment of symptoms of PE (i.e., exercising to the point of losing the control over such a behaviour, so that it may leads to physical, psychological, or social damage; Szabo et al, 2018 ). According to the findings from previous reviews conducted in the field of PE (e.g., Alcaraz-Ibáñez, Paterna, Sicilia, & Griffiths, 2020 , 2021 ), the following six key instruments were considered eligible: Commitment to Exercise Scale (CES), that assesses the extent to which (i) individuals’ well-being are influenced by exercising, (ii) adherence to exercise is maintained in the face of adverse conditions, and (iii) exercise regimen interferes with social commitments ( Davis, Brewer, & Ratusny, 1993 ); Compulsive Exercise Test (CET), which assesses the primary factors operating in the maintenance of excessive exercise within the eating disorders domain ( Taranis, Touyz, & Meyer, 2011 ); Exercise Addiction Inventory (EAI), which assesses six common criteria proposed for behavioural addictions ( Terry, Szabo, & Griffiths, 2004 ); Exercise Dependence Questionnaire (EDQ), which assesses elements employed in traditional models of addiction and both psychologically-related and socially-related consequences of exercise behaviour ( Ogden, Veale, & Summers, 1997 ); Exercise Dependence Scale (EDS-21), which assesses seven criteria adapted from substance abuse defined in the Diagnostic and Statistical Manual for Mental Disorders ( American Psychiatric Association, 1994 ) applied to the exercise domain ( Downs, Hausenblas, & Nigg, 2004 ); and Obligatory Exercise Questionnaire (OEQ), which assesses the subjective need to engage in repetitive exercise behaviours ( Pasman & Thompson, 1988 ). The eligibility of these instruments was also supported by the findings derived from a search on Google Scholar performed by the present authors for all the 17 measures previously identified within the field ( Sicilia, Paterna, Alcaraz-Ibáñez, & Griffiths, 2021 ).…”
Section: Methodsmentioning
confidence: 99%